THE APHTHARSIA IN THE PAULINE THOUGHT.A BIBLICAL ANTHROPOLOGICAL PERSPECTIVE - Jemna, Dănuţ-Vasile (Sacra scripta, 2012)
For biblical anthropology, the concept of aphtharsia (incorruptibility) plays an important role in the construction of a holistic vision about man, in accordance with the Hebrew tradition of the Old Testament. This vision is continued in the New Testament, especially in the Pauline texts. Entering the biblical literature of the New Testament by means of the sapiential books of the Old Testament, aphtharsia is a term used in the biblical text designating both God and man. This double stance of the term allows for the shaping of a biblical anthropological vision about man’s eternal destiny expressed in the patristic theology by means of the concept of theosis. The analysis of the occurrences of aphtharsia in the Pauline texts represents an important aspect of the research with regard to the place and role of this concept in the biblical thought about man, as well as the manner enabling the development of new contributions to the biblical anthropology.